2007
DOI: 10.1097/01.sla.0000245577.68151.bd
|View full text |Cite
|
Sign up to set email alerts
|

Combination of SELDI-TOF-MS and Data Mining Provides Early-stage Response Prediction for Rectal Tumors Undergoing Multimodal Neoadjuvant Therapy

Abstract: Serum proteomic analysis may represent an early response predictor in multimodal treatment regimens of rectal cancer. These data suggest that this novel, minimally invasive modality may be a useful adjunct in the multimodal management of rectal cancer, and in the design of future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 44 publications
0
34
0
1
Order By: Relevance
“…They found that serum samples taken 24/48 h after treatment could predict the ultimate pathologic response with 87.5% sensitivity and 80% specificity based on a pattern of 14 differentially expressed proteins. They concluded that techniques, such as SELDI-TOF-MS, capable of simultaneously detecting multiple markers might be able to predict response at an individual level [67]. Numerous other researchers have applied this technique for biomarker identification in breast, ovarian, colon, liver and gastric cancers with promising results [10,15,26,68].…”
Section: Mass Spectrometrymentioning
confidence: 96%
See 1 more Smart Citation
“…They found that serum samples taken 24/48 h after treatment could predict the ultimate pathologic response with 87.5% sensitivity and 80% specificity based on a pattern of 14 differentially expressed proteins. They concluded that techniques, such as SELDI-TOF-MS, capable of simultaneously detecting multiple markers might be able to predict response at an individual level [67]. Numerous other researchers have applied this technique for biomarker identification in breast, ovarian, colon, liver and gastric cancers with promising results [10,15,26,68].…”
Section: Mass Spectrometrymentioning
confidence: 96%
“…Although it allows highthroughput analyses, its use in biomarkers discovery is limited due to low-resolution [66]. Smith and co-workers employed this approach to detect early-stage response to treatment (neoadjuvant radiochemotherapy) in 20 patients with rectal tumors [67]. They found that serum samples taken 24/48 h after treatment could predict the ultimate pathologic response with 87.5% sensitivity and 80% specificity based on a pattern of 14 differentially expressed proteins.…”
Section: Mass Spectrometrymentioning
confidence: 98%
“…Ainda através da análise do sangue pela técni-ca de SELDI, Smith e cols 16 obtiveram sucesso em identificar os pacientes que apresentaram uma resposta completa à terapia neoadjuvante com uma sensibilidade de 87%.…”
Section: Proteômica: a Nova Fronteira?unclassified
“…Smith et al analyzed sera taken before and during course of treatment from 20 patients with rectal cancer in relation to response according to the Mandard tumor regression grade (TRG). Although the "optimal" pretreatment model performed poorly, a 14-peptide classifier in serum taken 24-48-hours after treatment resulted in sensitivity of 88% and specificity of 80% [60]. Applying an alternative 3-grade scale for response, Hayashida et al constructed a 4-peptide signature from profiles of 27 patients with squamous cell esophageal cancer.…”
Section: Radiation and Chemoradiation Therapymentioning
confidence: 99%
“…Three eligible studies evaluated profiling in relation to pathological response to neoadjuvant 5-FU-based chemoradiation [60][61][62]. Smith et al analyzed sera taken before and during course of treatment from 20 patients with rectal cancer in relation to response according to the Mandard tumor regression grade (TRG).…”
Section: Radiation and Chemoradiation Therapymentioning
confidence: 99%